Current constitutional control systems - Altamirano Portocarrero, José Carlos (2008)
The idea of the present article is to resemble the function that exerts the organisms or powers of the countries, to fulfill the transcendental mission of control of the constitutionality of the law and to ensure for the protection of the fundamental rights and the public freedom. The historical origins of the institution referred to the American system will be treated first, then it will be analyzed the antecedent in Austria, later on we will focus in the present regimes of the Latin American countries and we will conclude in the current system in our country.